Effectiveness of IoT Integrated Problem Based Learning Model on Students Creative Thinking Skills Abilities - Asrul Sani; Dewanto Dewanto; Heppy Sapulete; Via Yustitia; Adrie Oktavio; Tomi Apra Santosa; Ellina Rienovita (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to determine the effectiveness of the Internet of Things (IoT) integrated problem-based learning model on students' creative thinking abilities. This type of research is a meta-analysis research by evaluating the effect of the size of IoT-based problem-based learning models on students' creative thinking skills. Data search keywords are problem-based learning models; IoT-based problem-based learning model; and Students' creative thinking skills. Data collection techniques are through direct observation of journal databases and documentation. The eligibility criterion is that research comes from journals indexed by SINTA, Scopus and Web of Science; Research must be published in 2020-2024; Research obtained through mendeley database, google scholar, Researchgate; ERIC, and ScienceDirect, research related to the effectiveness of IoT-based problem-based learning models on students' creative thinking skills and research has complete data to calculate the value of effect size. Data analysis is a quantitative analysis by calculating the effect size value with the Microsoft Excel 2020 application. The results of the study concluded from 12 journals analyzed the application of the Internet of Things (IoT)-based problem-based learning model had a significant influence on students' creative thinking ability with an average value of effect size of 0.942 This finding provides important information for teachers, the application of the problem-based learning model exerts a high category of influence to improve creative thinking skills in the learning process.